2015
DOI: 10.1039/c4nr07422j
|View full text |Cite
|
Sign up to set email alerts
|

In situ synthesis of luminescent carbon nanoparticles toward target bioimaging

Abstract: This paper describes the in situ synthesis of single fluorescence carbon nanoparticles (FCNs) for target bioimaging applications derived from biocompatible hyaluronic acid (HA) without using common conjugation processes. FCNs formed via the dehydration of hyaluronic acid, which were obtained by carbonizing HA, and partially carbonized HA fluorescence carbon nanoparticles (HA-FCNs), formed by a lower degree of carbonization, show good aqueous solubility, small particle size (<20 nm) and different fluorescence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
49
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 49 publications
0
49
0
Order By: Relevance
“…12 These natural polymers are composed primarily of polysaccharides, which are rapidly condensed in the presence of strong acids to form carbon dots with a certain degree of homogeneity in their optical properties and dimensions. 9,13,14 However, researchers often overlook the presence of trace amounts of phenolic compounds which are found in various polysaccharide backbones of plants and fruit. 15 …”
mentioning
confidence: 99%
“…12 These natural polymers are composed primarily of polysaccharides, which are rapidly condensed in the presence of strong acids to form carbon dots with a certain degree of homogeneity in their optical properties and dimensions. 9,13,14 However, researchers often overlook the presence of trace amounts of phenolic compounds which are found in various polysaccharide backbones of plants and fruit. 15 …”
mentioning
confidence: 99%
“…Transmission electron microscopy (TEM) images of (a) C-FNPs and (d) P-FNPs were assigned to C-C, C-O, C = O, and O-C-O, respectively. [19,23] The shift of binding energy peaks for P-FNPs (C-O, C-C, and C = C) confirmed that the C-FNPs were covered by PEG chains. The C-O binding in the area 286 eV after surface passivation demonstrated lower intensity, indicating that the C-O binding was functionalized using the carbon chain in PEG, which was further proven by an increase in the C-C binding.…”
Section: Resultsmentioning
confidence: 93%
“…Moreover, the number of sp 2 and delocalized electrons in the FNP surface confers the optoelectronics properties. [19][20][21][22] The fluorescent quantum yield (%) is estimated to be about 0.131% for blue and 0.228% for green FNPs as well as 0.398% for blue and 0.252% for green P-FNPs. Interestingly, the P-FNPs showed similar fluorescence profiles to the C-FNPs, but generated higher fluorescent intensities, consistent with the increased quantum yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescent carbon dots (CDs), such as graphene quantum dots (1)(2)(3)(4)(5), carbon nanodots (6)(7)(8)(9)(10) and polymer dots (PDs) (11,12), have attracted a great deal of interest from academia and industry due to their low toxicity, biocompatibility, photostability and scalability. PDs are being developed to replace carbon dots (CDs) in various applications, including chemical/biosensing, bioimaging, nanomedicine and as nanocatalysts (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%